Examining Delineated Competencies within Blended Hospital/Health System Pharmacy and General Medicine Advanced Pharmacy Practice Experiences - Jennifer L. Prisco; Yulia A. Murray; Tewodros Eguale; Jennifer D. Goldman (MDPI AG, 2024)
In the United States, Doctor of Pharmacy (PharmD) programs are required to provide advanced pharmacy practice experiences (APPEs) in the core inpatient rotation areas of hospital/health system pharmacy and inpatient general medicine patient care. Colleges and Schools of Pharmacy (C/SOPs) nationwide are increasingly utilizing blended or longitudinal APPE models to offer experiential opportunities; however, there is a gap in the literature to support programs with delineating rotation-specific competencies when integrating two or more rotations together. Utilizing a survey instrument, PharmD students at two C/SOPs reported their onsite inpatient rotation sub-competency activities achieved within the four competency areas of Hospital/Health Pharmacy Systems, Medication Safety and Quality, Clinical Applications, and Professional Practice, which are listed in Appendix C of the 2016 Accreditation Council for Pharmacy Education Standards Guidance Document. Unpaired two-sample t-tests were performed to compare proportions of sub-competency activity occurrence in the two rotation settings. In total, 168 students reported inpatient activities related to the four competency areas, with 95-100% reporting their involvement in one or more sub-competency opportunities within each area. Of the 26 sub-competencies compared, 73% significantly facilitated the development of competency to a greater extent for one APPE inpatient rotation type over the other (p < 0.05). The findings can be utilized by C/SOPs to support the delineation of rotation-specific competencies when blending inpatient experiential opportunities.